Knowledge, attitudes and practices on oral hygiene of mothers of children from 1 to 2 years frequent to The Sangolquí Health Center, Quito, Ecuador - Jaramillo, Nathalia (2017)
Objective: To evaluate the oral health knowledge of mothers of children under two years of age who attended a health center in the city of Sangolquí, Rumiñahui, province of Pichincha (Ecuador), between February and August 2015. Materials and method: 64 mothers randomly selected, after signing the informed consent and verification of compliance with the established inclusion criteria, were questioned about knowledge, practices and attitudes regarding the oral hygiene of their children and also about their socioeconomic conditions. Results: 31.25% reported an age between 26 to 30 years, 35.94% married civil status, current higher education was the most frequent level in 31.25%. The Chi square test showed that there is no correlation between mother's age and knowledge level (p = 0.198), showing that there is a statistically significant correlation between mothers' oral hygiene knowledge and the degree of instruction achieved by them = 0.015). Conclusion: Under the conditions of the present study, it can be concluded that mothers of children under two years of age who attend a health center in the city of Sangolquí, Rumiñahui province, province of Pichincha between February and August 2015 have a Regular level of knowledge regarding oral hygiene in their children.